Kajian residu antibiotik pada hati ayam di kota Yogyakarta=Study on Antibiotics in Chicken Liver in Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The objectives of this study was to reveal the prevalence of antibiotics residues, namely penicilline, macrolide, aminoglycoside and tetracycline groups, in the liver of chickens sold in traditional markets in the city of Yogyakarta. A total of 65 liver samples were taken proportionally by means of simple random sampling from 6 traditional markets in the city. The samples were qualitatively examined in the Disease Investigation Center in Wates, Yogyakarta. Factors studied included the breed of the chickens (broilers, culled layers and native chickens), slaughter facilities, the origin of the chickens and the location of the market. The result showed that the prevalence of the antibiotic residues in the city of Yogyakarta was respectively 29,23 % for penicillin, 36,92% for macrolide, 1.54% for aminoglycoside, and 26.15% for tetracycline. The chi-square (c2) test showed that the variable of species gave a significant difference frequency of the antibiotic residue of penicillin (c2 = 6.16, P=0.0460) and macrolide (c2 = 8.47, P=0.0144). Meanwhile the variable of market location gave a significant difference frequency of the antibiotic residue of penicillin (c2 =11.28, P=0.0461). The variable of slaughtering house, and the chicken liver source didn't give significant difference frequency, indicated by P>0.05 and smaller value for the chi-square (c2).